PLANNING COST PRODUCTION PATROL BOAT TYPE V21 FIBER GLASS - Hatuwe, M Rusdy; Marasabessy, Amir; Prayitno, Sugeng (Bina Teknika, 2017)
Development of fleet of patrol boats by the Ministry of Sea Transportation as an effort to supervise Indonesian territorial waters, especially in remote areas to prevent illegal fishing by neighboring fishing vessels where from October 2014 to 1 April 2017 there are 317 fishing vessels of neighboring countries that have been drowned, with details of Vietnam 142 vessels, Philippines 76 ships, Thailand 21 ships, Malaysia 49 ships, Indonesia 21 ships, Papua New Guinea 2 ships, China 1 ship, Belize 1 vessel and no country 4 ships Production cost planning needs to be carefully scrutinized, if the production cost budget is too big ship production Not economical otherwise if too small can affect the quality of ship production. The objective of the research is to make a budget production plan of V21 patrol boat type of fiber glass material, where the material and equipment of ship component is marine use with the price referring to current rupiah exchange rate, so it is expected to be guaranteed economic value and ship production quality. The method used in production cost planning is the unit price survey of materials and equipment / equipment of ship components with reference to general arrangement design drawings, mindset section and technical specifications. Based on the result of research, production cost of ship patrol vessel type V21 fiber glass Rp.554.720.000, - while the cost of making molded and hull and deck unit Rp.174.220.000, -